Britannica Book of The Year 1995 - Charles P. Trumbull (Chicago Encyclopaedia Britannica Inc., 1995)
Copyright Under International Copyright Union
Encyclopaedia Britannica Inc. Chicago Auckland/London/Madrid/Manila/Paris/Rome/Seoul/Sydney/Tokyo/Toronto
Keywords: Encyclopedias (3GdehShYGJs; General